2018
DOI: 10.1177/1609406918758086
|View full text |Cite
|
Sign up to set email alerts
|

Challenges When Using Grounded Theory

Abstract: The grounded theory (GT) method is widely applied, yet frequently misunderstood. We outline the main variants of GT and dispel the most common myths associated with GT. We argue that the different variants of GT incorporate a core set of shared procedures that can be put to work by any researcher or team from their chosen ontological and epistemological perspective. This “shared core” of the GT method is articulated as the principles of (1) taking the word “grounded” seriously, (2) capturing and explaining con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
120
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(129 citation statements)
references
References 40 publications
2
120
0
7
Order By: Relevance
“…We approached our data analysis utilizing grounded theory. We centered our approach based on Timonen, Foley, and Conlon's [63] synthesis of the most common and valuable principles of grounded theory in practice. These authors identified four "core principles" that we followed in our approach.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We approached our data analysis utilizing grounded theory. We centered our approach based on Timonen, Foley, and Conlon's [63] synthesis of the most common and valuable principles of grounded theory in practice. These authors identified four "core principles" that we followed in our approach.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that the research is actually grounded, meaning that any hypotheses are derived from the data, with existing knowledge being 'put in dialogue' with any emergent directions. Another core principle is identifying social processes and interactions specifically in terms of the action they have in the context of the field site [63]. Next, is the process of engaging in constant comparison of the data to other data in order to identify differences, similarities, and patterns across the corpus [63].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations